The Impact Of Hospital Information Systems (His) On Quality Of Care And Patient Safety : A Systematic Review And Meta-Analysis - Nofiyanti, Ayu Lestari; Malik, Kosasih, Rahadian; Pramarta, Vip; Nugroho, Taufan; Yuliaty, Farida (Journal of Neonatal Surgery, 2025)
Background: Hospital Information Systems (HIS), including Electronic Medical Records (EMR) and integrated hospital management platforms, have been widely adopted to enhance healthcare quality and patient safety. Despite their increasing implementation, comprehensive and consistent evidence regarding their real-world impact remains limited. Objective: This systematic review and meta-analysis aimed to evaluate the effectiveness of HIS in improving care quality and patient safety, while exploring human, organizational, and technological factors influencing implementation outcomes. Methods: A systematic literature search was conducted across PubMed, Scopus, Web of Science, and Google Scholar for studies published between 2010 and 2025. Twenty-two eligible studies covering various HIS types, study designs, and hospital settings were included. Due to methodological heterogeneity, data were synthesized narratively. Risk of bias was assessed using the Cochrane and ROBINS-I tools. Results: Most studies reported that HIS implementation improved data accuracy, workflow efficiency, and clinical decision-making, leading to enhanced quality of care. HIS also facilitated incident reporting, reduced documentation and medication errors, and supported regulatory compliance, thereby improving patient safety. Key challenges included increased nurse workload, underreporting of safety incidents, and user resistance. Critical success factors identified were user satisfaction, leadership engagement, training, and robust technological infrastructure. Conclusion: HIS significantly enhances healthcare quality and patient safety when supported by strong organizational readiness and user engagement. While evidence supports its benefits, barriers such as usability issues and cultural resistance must be addressed. Future research should focus on long-term outcomes, cost-effectiveness, and strategies to improve adoption, especially in resource-limited settings.